Karakteristik Remaja Putri dengan Dismenore di SMA Muhammadiyah 2 Bandar Lampung - Ike Ate Yuviska; Dewi Yuliasari (Universitas Malahayati Lampung, 2024)
ABSTRAK Dysmenorrhea or menstrual pain is a common problem that occurs in almost all women of reproductive age in the world, this is evidenced by research based on the World Health Organization (WHO) (2016) in Lail (2019), which shows the number of dysmenorrhea in the world is very large, on average more than 50% of women in each country experience dysmenorrhea. In Indonesia itself, the incidence of dysmenorrhea is quite large, showing sufferers reaching 60-70%. The incidence of dysmenorrhea in Lampung Province is estimated to be 1.12% - 1.35%. Based on the results of a pre-survey at SMA Muhammadiyah 2 Bandar Lampung on Tuesday, February 28, 2023, it was found that out of 15 students, 14 (93%) students said they had menstrual pain and 1 (7%) student said they did not experience menstrual pain. This research method is a type of quantitative research. In this study, the population was all young women in class XI IPA who experienced Dysmenorrhea in the last 3 months, totaling 47 female students. The sample in this study was female adolescents in class XI IPA who experienced Dysmenorrhea in the last 3 months totaling 47 female students. The results of this study showed that adolescent girls with Dysmenorrhea based on Menarce characteristics were 28 respondents (59.6%). Adolescent girls with Dysmenorrhea based on the characteristics of Menstrual Duration as many as 35 Respondents (74.5%). Adolescent girls with Dysmenorrhea with the characteristics of Exercise Routine were 27 respondents (57.4%). Adolescent girls with Dysmenorrhea based on the characteristics of Nutritional Status were 29 respondents (61.7%). Adolescent girls with Dysmenorrhea based on the characteristics of Strees as many as 12 (25.5%). It is recommended that young women who experience desminorrhoea increase their knowledge about desminorrhoea so that they can overcome the problem of desminorrhoea according to the cause. Keywords: Characteristics, Dysmenorrhea ABSTRAK Dismenore atau nyeri haid merupakan masalah umum yang terjadi pada hampir seluruh wanita usia reproduksi di dunia, hal ini dibuktikan dengan adanya penelitian berdasarkan Badan Kesehatan Dunia Word Health Organization (WHO) (2016) dalam Lail (2019), yang menunjukan angka dismenore di dunia sangat besar, rata-rata lebih dari 50% perempuan disetiap Negara mengalami dismenore. Di Indonesia sendiri kejadian dismenore cukup besar, menunjukan penderita mencapai 60-70%. Angka Kejadian Dismenore di Provinsi Lampung di perkirakan 1,12% - 1,35% Berdasarkan hasil pra survey di SMA Muhammadiyah 2 Bandar Lampung pada Selasa, 28 Februari 2023 ditemukan dari 15 siswi sebanyak 14 (93%) siswi mengatakan nyeri haid dan 1 (7%) siswi mengatakan tidak mengalami nyeri haid. Metode penelitian ini termasuk jenis penelitian kuantitatif.Pada penelitian ni yang menjadi populasi adalah semua remaja putri kelas XI IPA yang mengalami Dismenore 3 bulan terahir yang berjumlah 47 siswi. Sampel dalam penelitian ini remaja putri kelas XI IPA yang mengalami Dismenore 3 bulan terahir yang berjumlah 47 siswi. Hasil penelitian ini menunjukan Remaja putri dengan Dismenore berdasarkan karteristik Menarce sebanyak 28 responden ( 59,6%). Remaja putri dengan Dismenore berdasarkan karateristik Lama Menstruasi sebanyak 35 Responden (74,5%). Remaja putri dengan Dismeneore dengan karakteristik Rutinitas Olahraga sebanyak 27 responden (57,4%). Remaja putri dengan Dismenore berdasarkan karakteristik Status Gizi sebanyak 29 responden (61,7%). Remaja putri dengan Dismenore berdasarkan karakteristik Strees sebanyak 12 (25,5%). Disarankan remaja putri yang mengalami desminore untuk dapat meningkatkan pengetahuan mengenai desminore agar dapat mengatasi masalah desminor sesuai dengan penyebabnya. Kata Kunci: Karakteristik, Dismenore